Stabilitas warna basis akrilik gigitiruan lepasan setelah pembersihan dengan ekstrak dan infusa bunga rosella(Color stability of removabl - Irfany Irfany; Moh. Dharmautama; Ike Damayanti (DiscoverSys Inc., 2014)
The efficacy of rosella which are for bacteriostatic purposes and contain anthocyanin pigments as antioxidant, vitaminand minerals. There are so many benefits of rosella that it is necessary to develop alternative product of Rosellabesides as food and beverages. One of the alternatives is as herbal disinfectant for removable denture acrylic. The aimof the study is to observe the color changes of removable denture acrylic base after using extract and infusion ofRosella as denture cleanser. Each of 5 full dentures were utilized to observe the color changes before and after usingRosella extract with concentration 2.5%, 5%, 7.5 %,and 10% and also infusion with concentration 5% , 10%, and 20% . The values were obtained and inserted into the formula ∆E*ab = [(∆L*) 2+ (∆a*)2+ (∆b*). The results wereanalyzed by using Kosmorogrov and T-test. The study showed the extract of Rosella which have concentration 2.5%,5%, 7.5% and 10%, and infusion concentration 5%, 10%, and 20%, did not show significant difference in colorchanges (p<0.05). There are significant differences of color between intaglio and polished surfaces in color absorption(p<0.05). It was concluded that there are color changes, but not significant, in using extract and infusion of Rosella.